Substandard antibiotics and their clinical outcomes among hospitalized patients in southern Malawi: a pilot study - Chiumia, Francis Kachidza; Sinjani Muula, Adamson; Chimimba, Frider; Nyirongo, Happy Magwaza; Kampira, Elizabeth; Khuluza, Felix (Frontiers in Pharmacology, 2025)
BackgroundThe burden of substandard antibiotics is high in low-middle income countries including Malawi. These poor-quality antibiotics may cause deleterious effects on patients and promote drug resistance. We assessed the quality of antibiotics and the associated clinical outcomes among hospitalized patients in southern Malawi.MethodsA cross-sectional study involving review of retrospective records was conducted among hospitalized adult patients at Zomba central, Machinga and Nsanje district hospitals in October 2022 and January 2024. Trained pharmacy personnel recorded the parenteral antibiotics that were issued to the medical wards. We used these records for matching and sampling of the administered medicine batches to the patient files. In total, we reviewed 224 patient management files for eligible patients, aiming to assess the patient recovery and the occurrence of adverse drug reactions (ADRs) using a global trigger tool. We collected nine medicine samples of ceftriaxone and benzylpenicillin which were administered to these patients and subjected them to tests for the content of active pharmaceutical ingredients using methods adapted from the United States Pharmacopeia. For each sample, we collected at least ten dosage units and used Agilent® 1120 High Performance Liquid Chromatography for quality analysis.ResultsOf the 224 reviewed files, ADRs occurred in 18.3% % (n = 41) of patients while 12.05% (n = 27) did not recover from their illness. One benzylpenicillin sample was found out of specifications with only 61.8% of declared amount of active ingredients. Among patients who received benzylpenicillin with optimal API content, 15.8% experienced ADRs while 10.5% failed to recover from illness. For patients who received benzylpenicillin containing lower than required amount of API, only 7.1% experienced an ADR while 14.3% failed to recover from illness. These differences were, however, not statistically significant. Patient outcomes were significantly associated with the patient’s age and Charlson comorbidity index (CCI), p < 0.05.ConclusionThe present findings did not reveal statistically significant differences in patient outcomes based on the assessed medicine quality. Therefore, we recommend a larger prospective study to further validate these results and encourage stakeholders to be more vigilant on the quality of antibiotic medicines, as this is a crucial measure for improving clinical outcomes and preventing antibiotic resistance in Malawi.